El comportamiento sexual de personas adultas mayores mexicanas: estudio cuantitativo - Torrado Ramos, Amarilys Mercedes (2024)
The main objective of this quantitative study with a non-experimental cross-sectional design and descriptive scope was to identify the sexual behaviors present in senior adults living in Mexico City and their differences with respect to sociodemographic characteristics, sex, current relationship status, schooling, occupation and family life at home. The non-probabilistic and convenience sample consisted of 120 participating men and women aged 60 and over. The results reveal the presence of various dyadic and genitocentric sexual behaviors in the current sexual sphere of the participants. In addition, some differences are identified by sex (woman - man), education (high school, higher education and postgraduate), occupation (retired / or - worker and current relationship status (with a partner - without a partner).